2018
DOI: 10.18203/2394-6040.ijcmph20184790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of undiagnosed and uncontrolled diabetes mellitus among adults in South Chennai

Abstract: Background: Nearly 69.2 million people were living with diabetes as per 2015 WHO data. Prevalence of diabetes in Chennai is always on the rise and it nearly around 12%. The objectives of the study were to estimate the prevalence of undiagnosed diabetes and also to study about the uncontrolled diabetes among known case of diabetes.Methods: A cross sectional descriptive record based study done on 1361 adult population attending medical camps in various locations of South Chennai. The data regarding capillary blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 5 publications
7
7
1
Order By: Relevance
“…In our study, the limited sample size might have resulted in the higher prevalence of undiagnosed diabetes among healthy subjects than that reported in the literature: 10.3% among adults attending medical camps in Chennai and 7.2% among adults visiting health centres across eight Indian states. 17,18 Two-fourth of doctors was observed to have abnormal cholesterol level, similar to that reported among Indian physicians. 19 Moreover, this prevalence was significantly higher than that observed in the healthy subjects.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, the limited sample size might have resulted in the higher prevalence of undiagnosed diabetes among healthy subjects than that reported in the literature: 10.3% among adults attending medical camps in Chennai and 7.2% among adults visiting health centres across eight Indian states. 17,18 Two-fourth of doctors was observed to have abnormal cholesterol level, similar to that reported among Indian physicians. 19 Moreover, this prevalence was significantly higher than that observed in the healthy subjects.…”
Section: Discussionsupporting
confidence: 76%
“…Those who were known cases of Diabetes mellitus (Type 2) and Non-residents were excluded from the study. Simple random sampling method was adopted using the formulae 4pq/L 2 where P = 10% (Prevalence of undiagnosed diabetes mellitus in South Chennai)[8] and L is the absolute precision(5%)the sample size was calculated to be 150 after taking 10% non-response rate. [8] Medico-social workers attached to our department identified the residential area where the majority of them were insured persons of Employees state insurance act.…”
Section: Methodsmentioning
confidence: 99%
“…This finding was slightly more when compared to a study conducted by Rani et al in Mysuru, Karnataka in 2017 which showed a prevalence of 59% and it was almost similar to a study done in South Chennai in 2017 by Ganesh et al which showed 65.4% prevalence for uncontrolled blood sugar levels. 10,13] Another study done by Tripathy et al in Punjab also got similar results with 65% prevalence for uncontrolled diabetes. 14 It was observed that poor glycaemic status was seen more in patients with longer duration of disease which was similar to a study conducted in Jordan by Khattab et al in the year 2010.…”
Section: Discussionmentioning
confidence: 63%